Investigation of Breast Self-Examination Behavior Based on Transtheoretical Model in Middle-Aged Women Covered by Alborz Health Centers in 2018 - Marzieh Bayat Ghiasi, Seyedeh; Keramat, Afsaneh; Goli, Shahrbanoo (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Breast cancer is the most common cancer among women in the world and in Iran. The incidence of breast cancer in Iran is at least one decade lower than that in developed countries. Screening for prevention is the most important effort to improve health in diseases. Breast self-examination and breast examination by specialist physicians and mammography (40 years and older) are early diagnosis methods, among which self-examination is cost-effective. In this study, Prochaska etl.’s (1983) transtheoretical behavioral change model was used. The present study was conducted in 2018 with the aim of investigating the self-examination behavior based on the transtheoretical model in middle-aged women covered by Alborz health centers. Methodology: In this descriptive-analytical study conducted in 2018, 496 middle-aged women (30-59 years old) referred to Alborz health centers were selected by the stratified sampling method. To determine the stages of change in breast self-examination behavior, a checklist of the Prochaska model of breast self-examination behavior was used. This checklist includes stages to change the behavior in performing breast self-examination screening and the five stages of pre-contemplation, contemplation, preparation, action, and maintenance. To collect the data, the research subjects were included in the study after providing explanations for them about the objectives of the study, the confidentiality of the study, and the lack of need to write their name and address, and the data were analyzed through SPSS16 software. Results: In this study, 496 middle-aged women aged 30 to 59 years in Alborz province were studied. The age range of the subjects was 30 to 59 years, with a mean age of 47.13 years and a standard deviation of 8.52. The distribution of subjects in each of the stages of breast self-examination behavior change was 18.8% in the pre-contemplation stage, 23.8% in the contemplation stage, 29.4% in the preparation stage, 15.1% in the action stage, and 12.9% in the maintenance stage. The relationship between age and breast self-examination behavior was evaluated based on a transtheoretical model (in three stages of pre-contemplation (1), contemplation + preparation (2), and action + maintenance (3)) through one-way analysis of variance (p-value = 0.001). The results showed that this relationship was significant. Also, in this study, the relationship between education and breast self-examination behavior was investigated based on the transtheoretical model (in an integrated way: precontemplation, contemplation + preparation, action + maintenance) through the chi-square test. The relationship between marital status and breast self-examination behavior was investigated based on a transtheoretical model (contemplation and preparation were combined, and action and maintenance were combined), and their relationship was found to be significant (p-value = 0.016). The relationship between the history of familial breast cancer and breast self-examination behavior was investigated based on the transtheoretical (3-stage) model with the chi-square test. The test results showed a link between a familial history of breast cancer andeast self-examination (p-value = 0.005), and it was found that people with a familial history of breast cancer showed a higher level of self-examination in the pre-contemplation and preparation stages. Conclusion: The research results showed that most of the people were in the pre-action stage, and a small percentage of the participants were in the action and maintenance stages. Therefore, it is necessary to conduct educational interventions to inform women to promote breast self-examination behavior.